The Effect of Muscle Fatigue on Normal Biomechanics of Shoulder Girdle: A Systematic Review of the Literature - Razie Joghatin Alibazi; Afsoun Nodehi Moghadam; Vida Zarrabi; Enayatollah Bakhshi; Nazanin Nakhaei (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: Dynamic stability in shoulder is an important element in life and any disorder in muscular function which helps maintain this stability leads to shoulder pathology. One of these disturbing factors is fatigue. According to the research team information until now there has not been a study investigated systematically the effect of fatigue on shoulder girdle biomechanics. So the purpose of this systematic review is to determine the effect of muscle fatigue on normal shoulder girdle biomechanics. Materials & Methods: This study is a systematic review based on search in PubMed, Scopus, Elsevier, Ovid, CINAHL, Science Direct, ProQuest, Thompson, EMBASE and Medline databases for the period of 1995- 2012. The keywords used were Shoulder, Muscle Fatigue, Proprioception and Kinematics. Two levels of reevaluation were used on 350 citations. Results: The search strategy resulted in 350 results out of which 22 papers met the criteria for this study. Variation among studies in terms of sample size, fatigue protocol and method of measurement were investigated. Conclusion: Evidences demonstrated muscle fatigue leads to change in activation pattern of muscles shoulder girdle and consequently kinematics as well as reduction in proprioception during different positions and movements in both scapulothoracic and glenohumeral joints. Generally the results indicated that there are sufficient evidences based on the effect of fatigue on the muscular fatigue has disturbance effects on shoulder girdle kinematics and could alter the normal biomechanics.